PSYCHOSIS RISK ASSESSMENT FOR ADOLESCENTS IN CLINICAL PRACTICE - Kostic, Jelena Slavko; Žikić, Olivera; Đorđević, Vladimir; Stevanović, Sofija (Acta medicae Medianae, 2024)
The importance of Ultra High Risk (UHR) state for psychosis has been increasingly acknowledged to such an extent that Attenuated Psychosis Syndrome (APS) is being considered as a new diagnostic category in the DSM-5. The suggested criteria for attenuated psychosis syndrome presuppose the presence of at least one of three attenuated positive psychotic symptoms (disorganized speech, delusions and/or hallucinations) with a frequency of at least once weekly in the past month. These symptoms would exacerbate in the past year, cause disability, distress or help-seeking behavior, and could not be explained by another mental disorder. The paper aimed to present the assessment of attenuated psychosis syndrome in a male adolescent aged 17 and its implications in diagnosis and management. Apart from clinical examination, the assessment was performed using the Comprehensive Assessment of At-Risk Mental States (CAARMS version 2006) and the Social and Occupational Functioning Assessment Scale (SOFAS). Structured assessment of Attenuated Psychosis Syndrome, especially in adolescence, represents a delicate task for mental health professionals. It gives an opportunity to identify high-risk individuals for psychosis, provide early intervention targeting the present symptoms, reduce stress, improve functioning and at least delay the progression to the clinical picture of full-blown psychosis.
Keywords: psychosis risk, adolescence, attenuated psychosis syndrome, assessment